2018
DOI: 10.1159/000495961
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exosomal Long Non-Coding RNAs Serve as Biomarkers for Early Detection of Colorectal Cancer

Abstract: Background/Aims: Colorectal cancer (CRC) is the third most commonly diagnosed malignancy and the second leading cause of cancer-related deaths worldwide. Thus, methods for early diagnosis of CRC are urgently needed. We aimed to identify potential long non-coding RNAs (lncRNAs) in circulatory exosomes that may serve as biomarkers for the detection of early-stage CRC. Methods: Exosomes from the plasma of CRC patients (n = 50) and healthy individuals (n = 50) were isolated by ultracentrifugation, followed by extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…MiRNAs and lncRNAs play a vital role in regulating gene expression via their fine regulation at various levels, including transcription, translation and protein functions. Multiple miRNAs and lncRNAs not only can serve as biomarkers for diagnosis of multiple cancers, but also are involved in drug resistance [19][20][21][22][23][24][25][26]. Lots of ncRNAs have been found to be abnormally expressed in HCC and to be associated with the invasion, metastasis, drug resistance and radioresistance of HCC cells [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs and lncRNAs play a vital role in regulating gene expression via their fine regulation at various levels, including transcription, translation and protein functions. Multiple miRNAs and lncRNAs not only can serve as biomarkers for diagnosis of multiple cancers, but also are involved in drug resistance [19][20][21][22][23][24][25][26]. Lots of ncRNAs have been found to be abnormally expressed in HCC and to be associated with the invasion, metastasis, drug resistance and radioresistance of HCC cells [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…As for the asymmetric distribution of UCA1, it is hypothesized that tumor cells limit the secretion of UCA1 via exosomes to retain UCA1, which suggests that it has a crucial oncogenic function in CRC progression. Studies have demonstrated a significant overexpression of LNCV6_116109, LNCV6_98390, LNCV6_38772, LNCV_108266, LNCV6_84003, LNCV6_98602, and Colon cancer-associated transcript 2 (CCAT2) in CRC tissue, serum levels, and exosomes of CRC patients when compared to HC [116,117]. The levels of all the aforementioned lncRNAs, with the exception of CCAT2, were significantly altered in each stage [117].…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…Studies have demonstrated a significant overexpression of LNCV6_116109, LNCV6_98390, LNCV6_38772, LNCV_108266, LNCV6_84003, LNCV6_98602, and Colon cancer-associated transcript 2 (CCAT2) in CRC tissue, serum levels, and exosomes of CRC patients when compared to HC [116,117]. The levels of all the aforementioned lncRNAs, with the exception of CCAT2, were significantly altered in each stage [117]. Meanwhile, the higher expression of CCAT2 was associated with local invasion and lymph node metastasis.…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…The survival of CRC patients is closely related to the stage at diagnosis; therefore, there is an urgent need for early diagnosis for CRC prevention and successful treatment. The study performed by Hu et al [100] aimed to identify potential exosomal lncRNAs that may use as early stage biomarkers for CRC. Microarray studies identified a subset of 6 lncRNAs (LNCV6_116109, LNCV6_98390, LNCV6_38772, LNCV_108266, LNCV6_84003, and LNCV6_98602) significantly higher expressed in the plasma of CRC patients than in negative control individuals.…”
Section: Clinical Value Of Using Exosomal Lncrnas As Liquid Biopsiesmentioning
confidence: 99%
“…Furthermore, they analyzed the expression patterns in each stage of CRC and found the 6 lncRNAs significantly upregulated in stage I/ II of CRC disease. These authors concluded that the 6 lncRNA panel can be used as biomarkers for noninvasive screening of CRC with high sensitivity and specificity [100] . Li et al [36] also carried out an study to determine the usefulness of the exosomal GAS5 lncRNA (Exo-GAS5) as a biomarker for early stage nonsmall cell lung cancer (NSCLC) diagnosis.…”
Section: Clinical Value Of Using Exosomal Lncrnas As Liquid Biopsiesmentioning
confidence: 99%